Perancangan Sistem Pendukung Keputusan dalam Membaca Cepat untuk Menemukan Ide Pokok Paragraf - Nunu Kustian; Wanti Rahayu; Retna Ningsih (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2017)
Decision Support Systems (DSS) is a system that can assess the alternatives in order to help with the decision-making. Indonesian language lesson in Junior HighSchool, especially the topic of finding the main idea ina paragraph is still a focusIndonesian teachers keep as many students still have difficulty in understandinghow to find the main idea in a paragraph. Systems designed by using the method of Simple Additive Weighting (SAW) will perform to determine the selected speed reading techniques in finding the main idea in a paragraph. The data are analyzedbyevaluating the questionnaires in the form of questions given to population consisting of 36 students. The built systems help to resolve and speed up the selected techniques for finding a main idea in a paragraph.